2021
DOI: 10.7759/cureus.12652
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5-Fluorouracil in the Treatment of Pterygium

Abstract: To determine the efficacy of 5-Fluorouracil (FU) in the treatment of pterygium. Methodology After meeting the inclusion criteria 101 patients were enrolled in this study. Informed consent and demographic information was taken from all the patients. Patients underwent ophthalmic clinical examination that included slit lamp examination to grade pterygium. Before starting 5-FU injections, all topical medication was stopped. After four weeks the effects of 5-FU and its efficacy was noted. The patients were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…2 Although, the study conducted by Shah et al, had demonstrated no such adverse effect, our study revealed 3 cases of punctate epithelial keratitis in 5FU group but no such event was seen in Bevacizumab group. 3 Our study demonstrated the superior efficacy of 5FU as sole therapy in improving the clinical appearance of primary pterygium as compared to Bevacizumab, as reduction in grade of pterygium was seen in 21 (65.6%) patients in 5FU group versus only 2 patients (6.3%) in Bevacizumab group. However, since no other known study comparing the efficacy of the two treatment modalities is available, further studies are recommended to reach a definitive conclusion.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…2 Although, the study conducted by Shah et al, had demonstrated no such adverse effect, our study revealed 3 cases of punctate epithelial keratitis in 5FU group but no such event was seen in Bevacizumab group. 3 Our study demonstrated the superior efficacy of 5FU as sole therapy in improving the clinical appearance of primary pterygium as compared to Bevacizumab, as reduction in grade of pterygium was seen in 21 (65.6%) patients in 5FU group versus only 2 patients (6.3%) in Bevacizumab group. However, since no other known study comparing the efficacy of the two treatment modalities is available, further studies are recommended to reach a definitive conclusion.…”
Section: Discussionmentioning
confidence: 51%
“…All the patients who presented with primary pterygium were recruited in the study. The minimum required sample size was 64, calculated by using WHO sample size calculator, where proportion of successful outcome in terms of vascularity grade was considered to be 50%, proportion of successful outcome in exposed group was considered to be 86.7% 3 , with 80% study power, 95% level of confidence and 10% precision.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Said et al conducted a study in which it was presented that 93.3% of cases hada reduction of fibrovascular tissue and halting of growth after 0.1-0.2 ml or 2.5-5 mg 5 FU [32]. Low dose intra-operative 5-FU effectiveness was studied by Maldonado et al and concluded that it was inefficient in preventing reoccurrence however it may be due to low dosage as well as time span of treatment suggesting that only one injection may not be sufficient [33]. It wasalsofound by a studythat 5-Fluorouracil injection intra lesional also improved cosmetic appearance of not only primary but of recurrentpterygia as well [25].…”
Section: Fluorouracilmentioning
confidence: 99%